(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
This article deals with Yaldā, one of the most prominent national festivities of Iranian culture. It first reviews Yaldā’s background in history and mythology, then examines the approach of various Persian-speaking poets to the concept of Yaldā, and finally studies some of the folklore related to Yaldā that is common in different regions of Iran. The main question presented is whether it is possible to determine a specific historical origin for Yaldā. In Persian literature, what have different poets said about Yaldā, and have they mentioned its roots? Is Yaldā important because it has roots in ancient rituals? Yaldā is celebrated at a time of year when in pre-Islamic times, religious festivals such as Khorramrooz and Azarjshan were held. Various sources that have spoken about Mithraism have also mentioned the celebration of the birth of God Mehr at the beginning of winter in ancient Iran. However, it is not possible to say with certainty exactly which of these celebrations Yaldā is stemmed from and it may have been influenced by any of them. It appears that the celebration of the first night of winter in ancient times had more religious aspects, but due to the roots of those celebrations in past religions, elements such as fire have faded in the Islamic period, and Yaldā rituals emphasize family gatherings. Without the support of official institutions, this tradition has been kept alive by the general public and classes such as farmers. The public does not mention the festivals of ancient Iran or Mithraism during the Yaldā ceremony, and these notions are only encountered in articles and books. Today, the concepts associated with Yaldā are the emphasis on the importance of family and intimate relationships, friendship and reconciliation, and the importance of nature.